Hubungan Antara Life Style Dengan Prilaku Pengontrolan Tekanan Darah Pada Penderita Hipertensi - Fajriati, Yuri Rahma; Utomo, Wasisto; Dewi, Wan Nishfa (Indonesian Research Journal on Education, 2025)
Hypertension often presents without noticeable symptoms, causing individuals to be unaware that they have the condition. A person is considered hypertensive when their blood pressure exceeds 140/90 mmHg. Lifestyle factors must be taken into consideration to reduce the incidence of hypertension. This study aims to determine the relationship between lifestyle and blood pressure control behaviors among individuals with hypertension. This research employed a quantitative approach with a descriptive correlational design and a cross-sectional method. The sample consisted of 98 hypertensive respondents selected based on inclusion criteria using a purposive sampling technique. Data were collected using a lifestyle questionnaire developed by the researchers, which had undergone validity and reliability testing, as well as digital sphygmomanometer measurements of blood pressure. Data analysis included univariate and bivariate analyses using the chi-square test. The results showed that the majority of respondents (41 individuals, 80.4%) with a good lifestyle had controlled blood pressure. Meanwhile, most respondents (46 individuals, 97.9%) with a poor lifestyle had uncontrolled blood pressure. Statistical testing indicated a significant relationship, with a p-value of 0.000 < α 0.05. It can therefore be concluded that a good lifestyle among individuals with hypertension is associated with better-controlled blood pressure.